Обґрунтування технології виробництва фруктово-овочевих гранул в системі натрію альгінат-кальцію фосфат - Калина, Вікторія Сергіївна; Kalyna, Victoriya; Тарабара, Марина Віталіївна; Tarabara, Maryna (Таврійський державний агротехнологічний університет, 2019)
У статті наведено гелеутворюючі властивості альгінату натрію та процес утворення структури гелю в розчинах альгінатів. Встановлено оптимальні рецептурні співвідношення інгредієнтів та розроблено технологію виробництва гранульованих напiвфабрикатiв у системі натрію альгінат–трикальцію фосфат з використанням сезонної плодово-ягiдної та овочевої сировини – соків. Визначено органолептичні показники якості альгінатних гранул на основі грушевого, морквяного та бурякового соків. The article presents the gel-forming properties of sodium alginate and the process of formation of the gel structure in alginate solutions. The optimal recipe ratios of ingredients have been established and the production technology of granulated semi-finished products in the sodium alginate-tricalcium phosphate system has been developed using seasonal fruit and vegetable and vegetable raw materials - juices. Determined the organoleptic quality indicators of alginate granules based on pear, carrot and beet juice. The process of syneresis is irreversible, developed fruit / vegetable granules based on sodium alginate can not be stored for a long time. It is recommended to use them immediately after cooking as an independent product or for decorating dishes.
Justification of technology of manufacture fruit / vegetable granules in the system sodium alginat – calcium phosphate
Keywords: фруктово-овочеві гранули; fruit and vegetable granules; система натрію альгінат–трикальцію фосфат; sodium alginate – tricalcium phosphate system; гранулювання; granulation